2011
DOI: 10.1002/jcop.20449
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effects of ethnic identification on the relationship between parental monitoring and substance use in mexican heritage adolescents in the Southwest United states

Abstract: The purpose of this study was to assess the combined effects of ethnic identification and perceived parental monitoring on the substance use of a sample of 162 male and 192 female Mexican heritage seventh grade adolescents. Parental monitoring predicted lower risk for substance use. An interaction of ethnic identification by parental monitoring was observed with parental monitoring exhibiting stronger effects in decreasing use of alcohol use among boys who scored low on ethnic identification. For girls, decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 42 publications
2
20
1
Order By: Relevance
“…The results of their systematic review found that parental monitoring, parent-child interaction, and child disclosure led to delayed alcohol initiation as well as reduced levels of later drinking [68]. Additional support for the findings of the current systematic review were found in the results of other studies which show that parental monitoring significantly decreases adolescent risk behaviour such as sexual risk behaviours and decreased substance use [26,56,60,67]. Furthermore, parental communication has been found to Unclear.…”
Section: Discussionsupporting
confidence: 76%
“…The results of their systematic review found that parental monitoring, parent-child interaction, and child disclosure led to delayed alcohol initiation as well as reduced levels of later drinking [68]. Additional support for the findings of the current systematic review were found in the results of other studies which show that parental monitoring significantly decreases adolescent risk behaviour such as sexual risk behaviours and decreased substance use [26,56,60,67]. Furthermore, parental communication has been found to Unclear.…”
Section: Discussionsupporting
confidence: 76%
“…This suggests that strong social and cultural norms are still inherent in rural Mexican culture. The differences found in the substance use initiation of these rural male and female respondents appears to be related to their stronger adherence to the traditional gender role of machismo and marianismo (Nagoshi, et al, 2011; Kulis et al, 2008). …”
Section: Discussionmentioning
confidence: 89%
“…Gender differences appear to be more salient among youth in rural communities where individuals tend to adhere to more traditional gender roles, and these social norms permit more substance use among males (Medina-Mora, 1994; Ozer & Fernald, 2008). The traditional gender role of machismo, for males, can emphasize engaging in risk-taking behaviors, thus potentially leading to substance use initiation at earlier ages and over time (Nagoshi, et al, 2011). For females, however, marianismo - the traditional notion that women’s primary obligation is to family, motherhood, and virtuosity (Kulis et al, 2008) - may be related to their delay of substance use initiation.…”
mentioning
confidence: 99%
“…In the U.S. adolescents of Mexican descent are the most rapidly growing adolescent ethnic group, have higher rates of substance use than non-Hispanic white students (Marsiglia, Kulis, Wagstaff, Elek, & Dran, 2005), and report higher rates of substance use than their counterparts in Mexico (Benjet et al, 2007; Delva et al, 2005). Studies in the southwestern U.S. consistently demonstrate that parental monitoring is negatively associated with substance misuse with higher rates of parental monitoring predictive of lower substance abuse among Mexican American adolescents (Nagoshi, Marsiglia, Parsai, & Castro, 2011) and Mexican American youths reporting greater parental closeness and increased parental monitoring less likely to rely on risky behaviors in order to cope with problems (Romero & Ruiz, 2007). Parental closeness is an important dimension of familismo or familism which has been identified as a potential protective cultural value in Hispanic cultures.…”
Section: Discussionmentioning
confidence: 99%